2021
DOI: 10.1177/0954411920987960
|View full text |Cite
|
Sign up to set email alerts
|

Research on coupling effects of actuator and round window membrane on reverse stimulation of human cochlea

Abstract: An active actuator of a middle-ear implant coupled to the round window membrane (RWM), which transmits vibration to the cochlea, has been used to compensate for hearing loss in patients. However, various factors affect the coupling condition between the actuator and the RWM, resulting in coupling leakage. In this study, a coupling impedance model of the human ear and the actuator was used to investigate the effect of inefficient coupling during reverse stimulation. First, the three-port circuit network model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Backside loading has been stressed as influencing the performance of an FMT in enhancing its vibratory performance and retention of long-term coupling ( 47 ). Using a coupling impedance model of the human ear, Xue et al ( 48 ) determined that poor coupling resulted in deterioration of responses across the entire frequency ranges with RW stimulation ( 48 ). Liu et al ( 49 ) using a human ear finite-element model comparison of sites of coupling of the RW membrane with that of the umbo, incus body, incus long process, and stapes demonstrated that for an equal force of stimulation applied, the RW produced more efficient cochlear response than equivalent magnitudes of force stimulating the other sites, such as the stapes footplate ( 49 ).…”
Section: Cadaveric Human Temporal Bone Studiesmentioning
confidence: 99%
“…Backside loading has been stressed as influencing the performance of an FMT in enhancing its vibratory performance and retention of long-term coupling ( 47 ). Using a coupling impedance model of the human ear, Xue et al ( 48 ) determined that poor coupling resulted in deterioration of responses across the entire frequency ranges with RW stimulation ( 48 ). Liu et al ( 49 ) using a human ear finite-element model comparison of sites of coupling of the RW membrane with that of the umbo, incus body, incus long process, and stapes demonstrated that for an equal force of stimulation applied, the RW produced more efficient cochlear response than equivalent magnitudes of force stimulating the other sites, such as the stapes footplate ( 49 ).…”
Section: Cadaveric Human Temporal Bone Studiesmentioning
confidence: 99%
“…Despite some success from RW stimulation, individual outcomes have shown much variability. Numerous animal and human cadaver experiments have explored the AMEI-RW coupling factors that might characterize the variability seen in patient outcomes clinically (3,10,14,(20)(21)(22) and in research (16,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These include the angle of AMEI approach, the static loading of the RW, the effects of interposed fascia, reduction of the RW membrane niche, and the size/shape of the AMEI tip (28,(34)(35)(36).…”
mentioning
confidence: 99%